From language shift to language revitalization and sustainability - Bastardas-Boada, Albert (Publicacions i Edicions de la Universitat de Barcelona, 2025)
This book aims to contribute to the overall, integrated understanding of the processes of language contact and their evolution, be they the result of political or economic (dis)integrations or migrations or for technological reasons. Via an interdisciplinary, holistic approach, it also aims to support the theoretical grounding of a unified, common sociolinguistic paradigm, based on an ecological and complexity perspective. This approach built on the fact that linguistic structures do not live in isolation from their social functions and must be situated in relation to the sub-and supra-systems that determine their existence if we are to understand their fortunes. It is a useful contribution to understanding and promoting the processes of linguistic revitalization in the world, combining at the same time the maintenance and development of diversity while ensuring the intercommunication of human species.